The fallacy of science is science: the impact of conflict of interest in vaping articles - Dèsirée Vidaña-Perez; Luz Myriam Reynales-Shigematsu; Erick Antonio-Ochoa; Sandra L. Ávila-Valdez; Inti Barrientos-Gutiérrez (Pan American Health Organization, 2022)
Objective. To explore the association between reporting conflict of interest (COI) and having a positive outcome toward vaping in scientific articles. Methods. A cross-sectional study that analyzed a sample of 697 articles published between 2017 and 2020 regarding vaping. Information on the reporting of COI, type of COI (no conflict, conflict with the tobacco industry, pharmaceutical industry, or other), and country of publication were collected. To explore the association between reporting COI and having a positive result for vaping, two logistic regression models were fitted, both adjusted by country of publication. Results. From 88 articles that reported COI, 23 reported COI with the tobacco industry, 44 with the pharmaceutical industry, and 21 reported another type of conflict. We found that reporting any type of COI increased by 4.7 times the odds (OR 4.70; 95% CI [2.89, 7.65]) of having a positive result for vaping. Additionally, compared to other countries, manuscripts published in England had 2 times higher odds (OR 2.40; 95% CI [1.16, 4.98]) of reporting a positive result for vaping. Reporting COI with the tobacco and pharmaceutical industries increased the odds of favorable results by 29 times (OR 29.95; 95% CI [9.84, 90.98]) and 2 times (OR 2.87; 95% CI [1.45, 5.69]), respectively. Conclusions. In scientific articles, reporting COI and having positive results for vaping are highly associated. COI should be considered and caution should be exercised when using data for policy-making.